Response and responsibility: Mainstream media and Lucy Meadows in a post-Leveson context. (February 2019) - Gupta, Kat
In this article, I focus on misgendering through pronoun use through a case study of news reporting on Lucy Meadows. I collect two corpora of newspaper articles and use these to identify keywords – words that occur more frequently in the Lucy Meadows texts than might be expected from examining the collection of general news texts. I explore patterns of pronoun use in the media representation of Lucy Meadows, and argue that press misgendering can take more subtle forms than the reporter's use of 'inappropriate pronouns or placing the person's identity in quotation marks to dismiss the veracity of the subject's identity' (Trans Media Watch, 2011: 11). This article offers a detailed examination of strategies accounting for the majority of male pronoun use: selective quotation of key interviewees, repetition and metacommentary.